Implementation of the Use of Animation Media in Understanding Arabic Translation Techniques Using Behaviorist Learning Theory - Putra, Yoza Andi; Enramika, Tomi (International Journal of Education, Information Technology, and Others, 2024)
The high intensity of use of technological media is increasing rapidly. This encourages teachers to use animation media in learning Arabic to understand translation techniques through the behaviorist learning system. On this basis, this research aims to test the effectiveness of using animation media on understanding techniques for translating meaning through the implementation of behaviorism learning. This research uses a qualitative approach design to analyze the meaning translation techniques produced by students from animation media based on behaviorist learning. The data used were the scores of 24 students of the Arabic at IAIN Kerinci, while the analysis technique used was Milles and Hubberman's theory for qualitative data analysis. The results of research techniques show that the use of animation media to understand translating meaning through the application of behaviorist learning is effective in increasing students' grades, while in the process of understanding meaning there are 4 techniques in the animation media of the story of Umar bin Abdul Aziz. Research findings show that the use of animation media can provide students with the opportunity to analyze techniques for translating meaning and be creative in determining learning objects. This sample is limited in use, so researchers recommend that future research use a research design with more varied objects and samples.